Communications, Signal Processing, and Systems Proceedings of the 2018 CSPS Volume I: Communications - Liang, Qilian; Liu, Xin; Na, Zhenyu; Wang, Wei; Mu, Jiasong; Zhang, Baoju (Lecture Notes in Electrical Engineering, 2019)
This book brings together papers from the 2018 International Conference on Communications, Signal Processing, and Systems, which was held in Dalian, China on July 14-16, 2018. Presenting the latest developments and discussing the interactions and links between these multidisciplinary fields, the book spans topics ranging from communications, signal processing and systems. It is aimed at undergraduate and graduate electrical engineering, computer science and mathematics students, researchers and engineers from academia and industry as well as government employees.